SISTEM PEMILIHAN DAN KINERJA KEPALA SEKOLAH (STUDI KASUS PENGANGKATAN KEPALA SEKOLAH SMP MUHAMMADIYAH I SURAKARTA) - Sukidi, Sukidi (2011)
The Research Objectives are to: 1) describe a pattern or system of appointing the head of SMP Muhammadiyah 1 Surakarta, and 2) describe the performance of the principal of SMP Muhammadiyah 1 Surakarta, 3) describe the constraints that appear in the select and appoint a head of SMP Muhammadiyah 1 Surakarta. Benefits that can be drawn from this study is to contribute knowledge about the pattern or the appointment of principals and system performance of principals and what are the constraints faced in choosing the head of SMP Muhammadiyah 1 Surakarta. This study is a descriptive qualitative research with ethnographic research design. The research was conducted on SMP Muhammadiyah 1 Surakarta. Informant research include head subdin Dikpora Surakarta SMP, the principal of SMP Muhammadiyah 1 Surakarta,the school committees,the teachers, the staffs,the students of SMP Muhammadiyah 1 Surakarta, the Chairman of Assembly Dikdasmen PDM Surakarta, as well as the Regional Leadership Muhammadiyah Surakarta. Data collections methods are using depth interviews, observation, and documentation. Data analysis starts from (1) data reduction, (2) presentation of data, and data verification. The results of this study were: 1) The appointment of a headmaster SMP Muhammadiyah 1 Surakarta did not through a system that has been regulated in the Central Executive Board of Muhammadiyah Dikdasmen Number: 085/KEP/1.4/F/2009, regarding procedures for appointment and dismissal of the head and deputy principals Muhammadiyah. The rule is confirmed that the appointment of principals should be initiated from the netting of the teachers, but the reality is only at the discretion of the Regional Leadership Council Dikdasmen Muhammadiyah Surakarta who hold Roling principals, there is even an outside appointed from SMP Muhammadiyah 1 Surakarta. 2) As for the performance of their respective school principals are not the same, but basically all the principals who had served in SMP Muhammadaiyah1 Surakarta capable of being a motivator, administrator, dynamist, and capable of being a role model for teachers and employees of SMP Muhammadiyah 1 Surakarta. 3) Constraints are not applied the rules of the Central Executive Board of Muhammadiyah Dikdasmen Number: 085/KEP/1.4/F/2009, regarding procedures for appointment and dismissal of the head and deputy head of the Muhammadiyah school.